Odpowiedzi

Najlepsza Odpowiedź!
2010-03-20T14:40:10+01:00
2010-03-20T14:45:35+01:00
Postac iloczynowa ma wzor y=a(x-x1)(x-x2)
a=-2 miejsca zerowe to 3 i-4 czyli
y=-2(x-3)(x+4)
2010-03-20T14:46:34+01:00
F(x)=-2x²+bx+c
miejsca zerowe : dla 3 0=-2*3²+3b+c => 0=-18+3b+c
dla -4 0=-2*(-4)²-4b+c => 0=-32-4b+c
Układ równań:
0=-18+3b+c
0=-32-4b+c

0=-18+3b+c
c=32+4b
podstawienie:
0=-18+3b+32+4b
0=14+7b
7b=-14
b=-2
c=32-8
c=24

f(x)=-2x²+bx+c => f(x)=-2x²-2x+24
postać iloczynowa:
f(x)=a(x-x₁)(x-x₂)
x₁=3 x₂=-4 a=-2
f(x)=-2(x-3)(x+4)